MANAJEMEN BERBASIS SEKOLAH DALAM MENGEMBANGKAN DAN MEWUJUDKAN BUDAYA MUTU DALAMPENDIDIKAN SAINS - Prasetyo, Zuhdan K.; Slamet, Slamet (Jurnal Cakrawala Pendidikan, 2016)
The centralization and bureaucratic climate in the planning and process of national education management, which has been applied so far, cannot be maintained anymore to answer the effort of realizing the civil democracy. Democracy in the educational process has brought to it an implication of planning a decentralized educational management, which is felt to fulfill community more than govemment needs. By optimizing the role of decentralization in education and especially by implementing the school-based management as something creative formulated in a regional autonomy form, a quality culture must become a priority. It is because in the globalization era Indonesians must be able to face the challenges and demands in the future which get increasingly harder and harder. We are demanded to be not only a more developed country but also a more independent one and such a condition can be used as the foundation for the achievement of a prosperous community based on Pancasila and UUD 1945. The school-based management is hoped to be able to change the mediocre culture which has been adopted into the quality culture in the process of the educational management in facing the globalization era. In science education the contribution that can be given to such a change in culture must be in process skills behaviors. beliefs. values, and attitudes that always keep Indonesians in high quality condition. To keep the culture in its qualified condition, total quality management can be used. In related to PP No. 22 Tahun 1999 about regional autonomy, the implementation of the integrated quality management is accomplished by using the school-based management system. It is clear that the etIort to realize the qualified management in science education can be held. The regional autonomy and that kind of management convince us that all decisions or policies in the organization of education must be taken based on a standard quality throughout the role of the teacher, parents, society, supervisor, and university. Some standards that function as the watch-dogs of the quality of our national education must not merely be aimed at the competence of the student but also at the teaching and educational assessment standards in science education